Case report: Dupilumab therapy for alopecia areata in a 4-year-old patient resistant to baricitinib - Cai, Lu; Wei, Yi; Zhao, Min; Zhuo, Jia; Tao, Xiao; Lin, Mao (Frontiers in Medicine, 2023)
Alopecia areata (AA) is a non-scarring hair loss disorder. Alopecia totalis (AT) and alopecia universalis (AU) are the severe subtypes of AA. Age of onset before 6 years of age, disease duration of more than 1 year, and extensive alopecia involving more than 50% of the scalp (including AT or AU) suggest a poorer prognosis. Topical corticosteroids are the preferred first-line treatment for pediatric AA. While some treatments, such as intralesional corticosteroids, systemic steroids, contact immunotherapy with squaric acid dibutyl ester, and JAK inhibitors, showed efficacy in adults with AA, their safety profiles limit their use in pediatric AA patients. Dupilumab is a biologic that effectively addresses the patho-physiology of Th2 allergic diseases, and treats atopic diseases by inhibiting the helper Th2 immune axis. AA has been reported to be significantly improved with dupilumab for atopic dermatitis (AD) in children and adults. We report hair regrowth over all of the scalp, eyebrows, and eyelashes after 10 months of dupilumab therapy in a 4-year-old AU patient resistant to baricitinib.